Translational Research in Pancreatic Adenocarcinoma - Kaur, Gurbakhash; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is ranked as the fourth leading cause of cancer-related deaths in the United States despite intensive basic and clinical research over the last decade. In this paper we summarize the Abstracts #176, #234, and #206 presented at the 2014 ASCO Gastrointestinal Cancers Symposium focussing on BRCA 1 and 2 mutations, PABL gene mutations and expression of microRNAs to matrix metalloproteinase. There is an intense need for new findings in the translational research field with prognostic, predictive and therapeutic value. Image: Survival vs. intensity of microRNA-21 staining plus severity of cancer (Figure 1)